Gaya hipotaksis dan parataksis dalam kerangka nahu fungsian-sistemik (Jurnal Bahasa, 2006)
This study aims to describe the usage of hypotactic and paratactic in the Malay language, specifically in the relation between structure, meaning and style. In describing them, the style that is specific to the writer is analyzed in detail. The data is taken from the text Sungai Mengalir Lesu, written by National Laureate A. Samad Said. In the analysis of hypotactic and paratactic structures, this article applies the theoretical framework of the functional-systemic grammar. In the structural consideration, dependent and independent clauses are ana-lyzed taking into view the presence and absence of conjunctions. As for meaning, the analysis focuses on the meaning borne by expansion clauses in complex sentences viz. in elaborating or extending the mean-ing of the main clause. This analysis show that the paratactic struc-ture is more complex than that of the hypotactic, and the expansion clause is more dominant in usage in both types of complex sentences.